Detection of Anti-CagA Antibodies in Sera of Helicobacter pylori-Infected Patients Using an Immunochromatographic Test Strip. (9th December 2019) - Karakus, Cebrail; Ulupinar, Zeynep; Akbas, Fahri; Yazici, Duygu
Abstract: The cagA gene of Helicobacter pylori that encodes an immunodominant CagA protein provokes severe mucosal damage and acts as a risk factor for the development of peptic ulcer disease and gastric cancer. Our aim is to develop an immunochromatographic test strip (ICTS) using our previously developed recombinant CagA (rCagA) protein and anti-rCagA monoclonal antibody (Mab) for the detection of anti-CagA antibodies in sera of infected patients. The rCagA was firstly conjugated to gold nanoparticle and placed into the conjugate pad. A nonconjugated rCagA and anti-rCagA Mab (CK-02) were immobilized on the test line and control line, respectively. Biopsy and serum samples from 30 H. pylori -infected patients were used. The presence of cagA gene in biopsy samples was first detected by PCR (Polymerase Chain Reaction), and 22 patients were found positive while 8 were negative. When serum samples were tested by our developed ICTS, 21 were positive for anti-CagA antibodies while 9 were negative. The serum samples were also tested by a commercial ELISA (Enzyme Linked Immunosorbent Assay), and when compared to the ICTS a sensitivity of 95% and a specificity of 100% were obtained. The ICTS can be used for rapid detection of CagA-positive H. pylori infection instead of expensive, time consuming and laborious invasive approaches.